INTRAOPERATIVE RADIOFREQUENCY AND CRYOABLATION FOR ATRIAL FIBRILLATION IN PATIENTS WITH VALVULAR HEART DISEASE - N. Maghamipour N. Safaie (Acta Medica Iranica, 2007)
Patients with valvular heart disease and suffering atrial fibrillation of more than 12 months duration have a low probability of remaining in sinus rhythm after valve surgery alone. We performed intra-operative radiofrequency ablation or cryoablation as an alternative to surgical maze ІІІ procedure to create linear lesion lines for conversion of this arrhythmia to sinus rhythm. A total of 30 patients with valvular heart disease and chronic persistent atrial fibrillation underwent different combinations of valve surgery and concomitant maze procedure with radiofrequency or cryo probes. These patients aged 48.10 ± 9.84 years in radiofrequency ablation group and 51.10 ± 13.93 years in cryoablation group. Both atrial ablation with radiofrequency probes, needed 26.15 ± 3.67 min extra ischemic time and ablation by mean of cryo-probes needed an extra ischemic time of 29.62 ± 4.27 min. There was one in hospital death postoperatively because of respiratory failure but no other complication. 6 months after the operation, among 30 patients with both atrial ablations, 25 patients were in sinus rhythm, no patient had junctional rhythm and 5 patients had persistent atrial fibrillation. At 12 months follow up, freedom from atrial fibrillation was 85% in radiofrequency group and 80% in cryo group. Doppler echocardiography in these patients demonstrated atrial contractility in 70% of the patients. Intraoperative radiofrequency or cryo-ablation of both atriums are effective and less invasive alternatives for the original maze procedure to eliminate the atrial fibrillation, and can be done in patients with valvular heart disease without increasing the risk of operation.